An Analysis of K-12 School Reopening and Its' Impact on Teachers. (November 2020) - Lambert, Juli Anna; Trott, Kim; Baugh, Reginald F.
Teachers are vulnerable non-essential workers that continue to have significant misgivings about in-person school reopening. Dialogue around pandemic management has relatively neglected these concerns so far. This perspective offers a broad framework for risk assessment related to COVID-19 and in-person instruction. The accumulated general body of knowledge related to COVID-19 is particularized to the special dynamics of education. We highlight the impact of historic investments and underinvestment in education on the viability of adapting best practices to mitigate risk. Gaps in public health planning to supply educators with needed personal protective equipment and vaccination are explored. The challenges for low-income and minority-predominant districts receive special attention. We place these problems within the broader context of socioeconomic disparities and the societal consequences of the pandemic. The local level of community transmission, resources, and circumstances should dictate reopening dates. Without effective infection control, teachers are justified to fear infection. The transparency and scientific rigor that would allow teachers to assess their personal health risk and characterize the process for decision-making has been largely absent.